PENGEMBANGAN ALAT UNTUK PEWARNAAN BATIK WET ON WET - Libriani, Nino (Department of Home Economics, Faculty of Engineering, Universitas Negeri Semarang, 2014)
Tujuan penelitian ini adalah; (1) Mengetahui desain alat untuk pewarnaan batik WOW dalam skala laboraturoium; (2) Mengetahui desain alat untuk pewarnaan batik WOW dalam skala industri; (3) Mengetahui kualitas motif batik WOW yang dihasilkan skala industri.Metode penelitian yang digunakan yaitu, Research and Development (R & D), metode penelitian yang digunakan untuk menghasilkan produk tertentu, dan menguji keefektifan produk tersebut. Teknik pengumpulan data menggunakan metode observasi, dokumentasi dan kuesioner. Hasil penelitian dapat disimpulkan bahwa: (1) Pengembangan alat untuk pewarnaan batik memperoleh hasil analisis dapat digunakan dengan sedikit perbaikan. Menggunakan alat proses pewarnaanÂ lebih efisien; (2) Pewarnaan menggunakan alat dapat menghasilkan motif WOW yang bervariasi, gradasi warna dan bauran warna yang dihasilkan juga sangat baik. The purposes of this research were: (1) To determine the tool design for Wet On Wet (WOW) batik coloring in laboratorial scale; (2) To determine the tool design for WOW batik coloring in industrial scale; (3) To know the quality of WOW batik motif which was produced in industrial scale. The research method was Research and Development (R&D) which was the method to produce particular product and test the effectiveness of the product. The techniques of data collection were observation, documentation and questionnaire. The result of the research can be concluded that: (1) Tool development for batik coloring obtained result analysis can be used with little improvement. By using the tool, the process of coloring was more efficient. (2) The coloring by using tool produced various WOW motifs. The obtained color shades and mix were also very good. The purposes of this research were: (1) To determine the tool design for Wet On Wet (WOW) batik coloring in laboratorial scale; (2) To determine the tool design for WOW batik coloring in industrial scale; (3) To know the quality of WOW batik motif which was produced in industrial scale. The research method was Research and Development (R&D) which was the method to produce particular product and test the effectiveness of the product. The techniques of data collection were observation, documentation and questionnaire. The result of the research can be concluded that: (1) Tool development for batik coloring obtained result analysis can be used with little improvement. By using the tool, the process of coloring was more efficient. (2) The coloring by using tool produced various WOW motifs. The obtained color shades and mix were also very good. The purposes of this research were: (1) To determine the tool design for Wet On Wet (WOW) batik coloring in laboratorial scale; (2) To determine the tool design for WOW batik coloring in industrial scale; (3) To know the quality of WOW batik motif which was produced in industrial scale. The research method was Research and Development (R&D) which was the method to produce particular product and test the effectiveness of the product. The techniques of data collection were observation, documentation and questionnaire. The result of the research can be concluded that: (1) Tool development for batik coloring obtained result analysis can be used with little improvement. By using the tool, the process of coloring was more efficient. (2) The coloring by using tool produced various WOW motifs. The obtained color shades and mix were also very good.